KUALITAS PELAYANAN PUBLIK BIDANG ADMINISTRASI TENTANG PENGURUSAN KARTU TANDA PENDUDUK ELEKTRONIK (e-KTP) DI KECAMATAN AMPANA KOTA - Wahid, Selviana A.; Hasbullah, Hasbullah; Jahya, Dirja N. (Katalogis, 2018)
This research aims to find out the quality of public services administration of handling National Identity Card (e-ID) at Ampana Kota district. This research was a descriptive research using a qualitative. approach. The data were collected by observation, interview and documentation. The informants in this research consist of 4 people, 1 person is the head of Ampana Kota district as key informant, 1 section head of government. 2 user community support services as an informant. Data analysis technique used (1) Collection of data, (2) data reduction data presentation, verification conclusion. The theory used in this research is the theory Parasurahman that measure the quality of service, namely (1) reliability, (2) responsiveness, (3) assurance: empathy and direct evidence. The research results show that; (1) part of the public service at Ampana Kota district was not have facilities such as generators that less optimized, when the power fails, the service process will stop, it means people do not get service. This happens because oj limited funds and no funds provided by Touna regency for theprocurement process. (2) people are not satisfied with the services provided by the Ampana Kola district. In the aspect 0.[ reliability about reliable in handling public complaints. reliable in terms oj time and accuracy of the service process, (3) the employees who help people who need the service must communicate well, (4) the security in Ampana Kota district have shown efforts to improve the quality oj services related to providing security for the community by placing the parking attendants to participate in securing the circumstances in the parking, (5) the aspect oj empathy that given of Ampana Kota district is giving a pleasant impression. It can be seen Jrom the attitude of the officer who explain clearly the service procedure and accept criticism or suggestions well as introspection Jor better service.